Of course it's good! : aggressively delicious meals anyone can make and everyone will love - Secrest, Jessica (Page Street Publishing Co., 2026)
Prepare delicious meals with this no-frills, all-flavor recipe collection from Jessica Secrest, the wildly popular home chef known for her hostile humor and affordable recipes. Her long-awaited debut cookbook has an array of mouthwatering meals that focus on low-effort ingredients and techniques--think pre-shredded cheese, tater tots galore, and your handy-dandy slow cooker--so you'll have an endless source of recipes to feed your family without wasting time or money.